Penerapan Metode Instruksi Langsung (Direct Instruction) dalam Sistem Pembelajaran Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Kelas 3 SD - Sudirah Sudirah (Yayasan Darussalam Bengkulu, 2020)
The low learning outcomes of 3rd grade students at Public Elementery School 05 Mukomuko City in Mathematics subjects two-dimentional figure and their characteristics only 3 students (38%) who have the above grades of minimum criteria (KKM). With an average student evaluation score of 48. For this reason, it is necessary to improve learning to improve student learning outcomes. One effort to improve learning is the use of appropriate learning models with subject matter. In this case the researchers used a direct learning model (direct instruction) to improve student learning outcomes. Direct Learning Model is one of the active learning models that provides opportunities for students to share ideas, consider the most appropriate answers and answer questions verbally so as to foster student confidence in expressing ideas or answers in front of the class thus is expected to improve student learning outcomes. From the learning outcomes that researchers do turn out direct learning models (direct instruction) can improve student learning outcomes, this is evidenced by an increase in student learning outcomes in each study that researchers do. Learning that researchers do begins with the prasiklus stage which is carried out on Tuesday April 25 2017 with an average student learning outcomes of 50.8, improvement of the first cycle Tuesday May 2, 2017 the average student learning outcomes to 61, and improvement of Cycle II Tuesday 09 May 2017 the average student learning outcomes 81.5. Thus it can be concluded that using the direct learning model in Mathematics can improve student learning outcomes.